HAKIKAT MANUSIA MENURUT PANDANGAN ISLAM DAN BARAT - Siti Khasinah (Jurnal Ilmiah Didaktika, 2013)
This article describes the nature of human beings, their characteristics, their potentials, and the development of the potentials. Some philosophers claim that a human being is considered animal for having some tendencies that are believed similar to an animal. However, this argument is contradictive to what is believed by Muslim. Humans have certain characteristics that naturally different from animals. They also posses potentials (innate potentials or innate tendencies) that can be develop naturally through life-experience or artificially through formal instruction such as schools and other educational institutions.